Study of the fibrinolytic process in a patient with antiphospholipid syndrome. Issue 3 (April 2015) - Marchi, Rita; Garmendia, Jenny; Kanzler, Daniela; Fuenmayor, Jaheli
<x xml:space="preserve">Abstract</x> The antiphospholipid syndrome (APS) is an autoimmune disease characterized by the presence of antibodies against β2-Glycoprotein I (aβ2-GPI), cardiolipin (aCL) and lupus anticoagulant combined with venous or arterial thrombosis and/or foetal losses. A 28-year-old female was positive for aβ2-GPI, aCL, aPT (antibodies against prothrombin) and lupus anticoagulant. She had two miscarriages and a deep vein thrombosis event. The patient plasma fibrinogen and IgG concentrations were two times higher than control. Fibrinolysis was induced in vitro adding tPA, before clotting plasma with 0.03 or 0.6 IU/ml thrombin, and in purified system with normal fibrinogen in the presence of 0.5 mg/ml of patient or normal IgG. The APS patient had 1.5 and 1.9 times higher clot rate formation (CRL) and maximum absorbance (MaxAbsL) at both thrombin concentrations. At 0.6 IU/ml of thrombin, the patient delay on fibrin polymerization onset was corrected. The patient Lys50MA (time needed for 50% clot dissolution) was slower (P < 0.05) at 0.03 IU/ml of thrombin; however, the lysis rate was faster at both thrombin concentrations. After adjusting the polymerization and fibrinolytic parameters according to the sample plasma fibrinogen concentration, there were almost no differences between patient and control at 0.6 IU/ml. In an IgG-fibrinogen purified system, fibrinolysis was equivalent in the presence of patient or normal IgG. In conclusion, the patient IgG fraction has no inhibitors against proteins of the fibrinolytic pathway. The differences observed between the APS patient and the control were more evident at low thrombin concentration due to the presence of aPT.